Study of the impact of blast furnace process intensification by increasing the blast flow rate on the operating parameters of the blast supply and heating system - Gres , L.P.; Gupalo , O.V.; Yeromin , O.O; Radchenko , Yu.M.; Sulimenko , S.Ye. (Theory and Practice of Metallurgy, 2024)
The objective of the study is to investigate the effect of increasing the air blast flow rate on the operating parameters of the blast supply and heating system for the conditions of a blast furnace with a useful volume of 1754 m3. Methods. The authors used numerical methods for calculations of fuel combustion, heat and mass transfer, and gas dynamics to determine the operating parameters of the air blast supply and heating system at the "turbo-blower - hot-blast stoves -hot blast pipeline - blast furnace" sections. Results. It has been determined that ensuring a temperature of 1350 °C under the dome of hot-blast stoves requires the enrichment of blast furnace gas with natural gas to a content of 5.6 % natural gas in the mixture. Heating of the air blast flow rate, which is raised by 18.5 %, requires an increase of the heat output of the hot blast stoves up to the maximum and leads to a decrease of the hot blast air temperature by 30 °C. At the same time, the heat losses of the hot blast pipeline in the section "hot-blast stoves -blast furnace" almost do not change, while the flue gas flow rate and pressure losses in the flue gas path of the hot-blast stoves increase significantly. Since the evacuation of flue gases from the hot-blast stoves occurs mainly due to the pressure of the combustion components, it is recommended to use a centralized air supply with an air fan of higher capacity. The scientific novelty of the research lies in the revealed relationship between the air blast flow rate and the operational parameters of the heating system and its supply to the blast furnace. The practical value of the research includes the developed recommendations for ensuring the operation of the air blast supply and heating system under conditions of increasing consumption.